Tuesday

September 16, 2014

September 16, 2014

Posted by **Anonymous** on Friday, January 18, 2013 at 3:22pm.

- Allegbra -
**MathMate**, Friday, January 18, 2013 at 11:28pmUse the quadratic formula to get

a=-0.01

b=0.06

c=5.9

x=(-b±sqrt(b²-4ac))/(2a)

3±sqrt(599)

**Answer this Question**

**Related Questions**

Algebra - .04x + 720 - .06x > = 650 -.02x <= -70 x < = -70/-.02 x <...

Algebra - Please solve the inequality .04 x + .06(12000-x) >= 650 .04x + 720...

Algebra - Add polynomials 0.15x^4 + 0.10x^3 - 0.01x^3 + 0.01x^2 + x 1.25x^4 + 0....

math - write 1.06X as a sum

Math - x + y = 26000 .06x * .03y = 1080 x =

algebra - solve the following: 300e^.06x = 1500

Pre Calculus - use a calculator to find approximate solutions of the equation. 8...

math - I need help in solving this subtraction (0.06x^3-0.07x^2+0.04x)-(0.02x^3+...

algebra2 - (1.06)(.7x) = .742x (1.06x)(.7) = .742x . how do you compare these ...

!math (4) - The demand function for a certain brand of CD is given by p = −...